PENGEMBANGAN INSTRUMEN TES NUMERASI BERBASIS TIMSS BAGI SISWA KELAS IV SEKOLAH DASAR - Rohmah, Nur; Wasino; Yuwono, Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a TIMSS-based numeracy test instrument for fourth grade elementary school students through the stages of development research. This study also aims to prove the validity and test the reliability of the instrument, analyze the characteristics of the test instrument based on item responses, analyze the practicality and determine the numeracy profile of test takers. This research is a type of Research and Development (R&D with reference to the Four-D (4D) model, which consists of four stages. In the process of developing test instruments, student involvement was carried out in stages, namely, 19 students in the small-scale test trial and 90 students in the large-scale test trial stage. Data collection was carried out through several methods, such as interviews, distributing questionnaires, and giving tests. Data analysis was carried out using qualitative and quantitative approaches, where qualitative data was obtained from the results of the needs analysis, while quantitative data was obtained through expert assessments, the results of small-scale trials, and large-scale trials. The results showed that the TIMSS-based numeracy test instrument had content validity >0.80 on each item and instrument reliability level of 0.72. The value of agreement between experts based on the Intraclass Correlation Coefficient (ICC) test also showed a figure of 0.72. Based on item analysis using the Rasch model, test items are distributed in four levels of difficulty, namely very difficult questions of 13.3%, difficult 40%, easy 30% and very easy 16.7%. Overall, this instrument meets the item eligibility criteria and is considered suitable for use in measuring the numeracy skills of fourth grade elementary school students.